THE INFLUENCE OF SELF-ESTEEM ON CONSUMPTIVE BEHAVIOR IN PURCHASING COSMETICS ONLINE IN FEMALE STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, PADANG STATE UNIVERSITY, CLASS OF 2023 - Zelila Utami, Rezmi; Nurmina (Causalita, 2024)
This researcher's study examines the influence of self-esteem on consumptive behavior among female students at the Faculty of Economics and Business, Padang State University Class of 2023. The human tendency to buy unexpected things is consumptive behavior. The rise of online shopping is one of the reasons why someone can have consumptive behavior. This research uses quantitative research methods with a correlational design. There are 2 variables in this research, namely consumer behavior and self-esteem. Consumptive behavior has 3 aspects, namely impulsive buying, irrational buying and waste. Meanwhile, the self-esteem variable has 4 aspects, namely strength, significance, virtue and ability. Data was collected using a questionnaire with a purposive sampling technique. The population in this study was 307 students with the criteria of being an economics faculty student, shopping online more than 3 times a month and having used PayLater. The coefficient of determination (R Square) received a value of 0.041. This explains the magnitude of the influence between the independent variable and the dependent variable in this study, namely 4.1%, while the rest is explained by other causes outside the model. The conclusion of this research is that self-esteem influences consumer behavior in students from the Faculty of Economics and Business class 23.